Mycoplasma pneumoniae: Current Knowledge on Nucleic Acid Amplification Techniques and Serological Diagnostics - Loens, Katherine; Ieven, Margareta (Frontiers in Microbiology, 2016)
Mycoplasma pneumoniae (M. pneumoniae) belongs to the class Mollicutes and has been recognized as a common cause of respiratory tract infections (RTIs), including community-acquired pneumonia (CAP), that occur worldwide and in all age groups. In addition, M. pneumoniae can simultaneously or sequentially lead to damage in the nervous system and has been associated with a wide variety of other acute and chronic diseases. During the past 10 years, the proportion of LRTI in children and adults, associated with M. pneumoniae infection has ranged from 0% to more than 50%. This variation is due to the age and the geographic location of the population examined but also due to the diagnostic methods used. The true role of M. pneumoniae in RTIs remains a challenge given the many limitations and lack of standardization of the applied diagnostic tool in most cases, with resultant wide variations in data from different studies. Correct and rapid diagnosis and/or management of M. pneumoniae infections is, however, critical to initiate appropriate antibiotic treatment and is nowadays usually done by PCR and/or serology. Several recent reviews have summarized current methods for the detection and identification of M. pneumoniae. This review will therefore provide a look at the general principles, advantages, diagnostic value, and limitations of the most currently used detection techniques for the etiological diagnosis of a M. pneumoniae infection as they evolve from research to daily practice.